Development of learning videos at SDN 106104 Sambirejo - M. Maisyaroh; S. Syarifah; M. Mursid (Inovasi Kurikulum, 2024)
The lecture learning method sometimes makes students bored, so it is necessary to develop learning methods that are effective and fun for students. This research aims to determine the feasibility and effectiveness of using instructional videos in teaching my area, my pride, class V at SDN 106104 Sambirejo. This research is development research, which refers to the 4-D development model, which consists of 4 stages, namely the Define, Design, Development, and Disseminate stages. Data was collected through observation, interviews, validation questionnaires, and tests. Based on research results, the developed learning video was validated by material expert validators, obtaining a feasibility percentage of 95.38 percent, a very valid criteria. The results of the small group trial obtained a practicality percentage of 88.50 percent, very practical criteria. The field trials' results show the percentage of practicality was 91.57 percent, a very practical criteria. At the field trial stage, effectiveness was achieved at 100 percent classically, with a gain score of 0.615 classified as medium effectiveness criteria. The percentage increase in learning outcomes is 92 percent, meaning that learning videos can be effectively used in the learning process of my proud region in class V at SDN 106104 Sambirejo AbstrakMetode pembelajaran ceramah terkadang membuat peserta didik bosan, sehingga perlu dilakukan pengembangan metode pembelajaran yang efektif dan menyenangkan untuk peserta didik. Penelitian ini bertujuan untuk mengetahui kelayakan dan keefektifan penggunaan video pembelajaran pada pembelajaran daerahku kebangganku kelas V SDN 106104 Sambirejo. Penelitian ini merupakan penelitian pengembangan yang mengacu pada model pengembangan 4-D yang terdiri dari 4 tahapan yaitu tahap Define, Design, Development, dan Disseminate. Pengumpulan data dilakukan dengan observasi, wawancara, angket validasi dan tes. Berdasarkan hasil penelitian video pembelajaran yang dikembangkan telah divalidasi oleh validator ahli materi memperoleh persentase kelayakan sebesar 95,38 persen kriteria sangat valid. Hasil uji coba kelompok kecil memperoleh persentase kepraktisan sebesar 88.50 persen kriteria sangat praktis. Hasil uji coba lapangan persentase kepraktisan sebesar 91,57 persen kriteria sangat praktis. Pada tahap uji coba lapangan keefektifan tercapai dengan 100 persen secara klasikal, dengan hasil gain score sebesar 0,615 diklasifikasikan dalam kriteria efektivitas sedang. Persentase peningkatan hasil belajar sebesar 92 persen, artinya video pembelajaran dapat efektif digunakan dalam proses pembelajaran daerahku kebangganku di kelas V SDN 106104 Sambirejo.Kata Kunci: 4-D; hasil belajar; video pembelajaran